Pentagonal Bipyramidal 3 d‐Metal Complexes Derived from a Dimethylcarbamoyl‐Substituted Pentadentate‐[N3O2] Ligand: Aiming for Increased Solubility. Issue 4 (24th January 2023) - Jubault, Valentin; Genevois, François; Pradines, Barthélémy; Cahier, Benjamin; Jbeli, Wejden; Suaud, Nicolas; Guihéry, Nathalie; Duhayon, Carine; Pichon, Céline; Sutter, Jean‐Pascal
Abstract: A pentadentate‐[N3 O2 ] ligand, H2 L NMe2, formed by condensation of diacetyl pyridine and dimethylcarbamoyl hydrazide (i. e. Me2 NCONHNH2 ), is reported to yield mononuclear pentagonal bipyramidal (PBP) metal complexes with Cr III, Mn II, Fe II, Co II, and Ni II, that exhibit good solubility in a wide range of solvents as compared to the classically used H2 L R ligands. With Cu II, dinuclear complexes were obtained. The potassium salt of the deprotonated ligand, K2 L NMe2, was also characterized. The reported complexes consist of [CrH2 L NMe2 Cl2 ] ⋅ Cl; Cat[CrL NMe2 (CN)2 ] (Cat=K + or PNP + ); [MH2 L NMe2 (H2 O)2 ] ⋅ (ClO4 )2 with M=Mn II, Co II, or Ni II ; [FeH2 L NMe2 (MeCN)2 ] ⋅ (PF6 )2 ⋅ MeCN; [FeH2 L NMe2 (MeOH)X] ⋅ X (X=Br or I); [CuH2 L NMe2 2 (MeOH)(ClO4 )] ⋅ (ClO4 )3 ⋅ 1H2 O⋅1.75H2 O; [CuHL NMe2 ]2 ⋅ (ClO4 )2 ⋅ H2 O; and [CuH2 L NMe2 (H2 O)]2 ⋅ (ClO4 )4 ⋅ 5H2 O. The magnetic behaviors of the PBP derivatives were assessed, especially the zero‐field splitting (ZFS) characteristics for the Cr III, Fe II, Co II, and Ni II derivatives. The ZFS characteristics were also determined from ab initio theoretical calculations. The obtained values confirm those extracted from magnetic measurements. Abstract : A pentadentate‐[N3 O2 ] ligand, formed by condensation of diacetyl pyridine and dimethylcarbamoyl hydrazide is reported to yield mononuclear pentagonal bipyramidal metal complexes that exhibit good solubility in a wide range of solvents.